Mitochondrial sequences of Rhipicephalus and Coxiella endosymbiont reveal evidence of lineages co-cladogenesis. Issue 6 (24th April 2020) - Coimbra-Dores, Maria João; Jaarsma, Ryanne Isolde; Carmo, Anderson Oliveira; Maia-Silva, Mariana; Fonville, Manoj; da Costa, Daniela Filipa Ferreira; Brandão, Ricardo Manuel Lemos; Azevedo, Fábia; Casero, María; Oliveira, Ana Cristina; Afonso, Sónia Maria de Santana; Sprong, Hein; et al.
ABSTRACT: Rhipicephalus ticks are competent vectors of several pathogens, such as Spotted Fever Group Rickettsiae (SFGR) and many Babesia species. Within this genus, different R. sanguineus s.l. lineages show an unequal vector competence and resistance regarding some pathogenic strains. Current literature supports that tick endosymbionts may play an essential role in the transmission ability of a vector. Indeed, the microbial community of Rhipicephalus seems to be dominated by Coxiella -like endosymbionts (CLE). Still, their co-evolutionary associations with the complicated phylogeny of Rhipicephalus lineages and their transmissible pathogens remain unclear. We performed a phylogenetic congruence analysis to address whether divergent R. sanguineus s.l. lineages had a different symbiont composition. For that, we applied a PCR based approach to screen part of the microbial community present in 279 Rhipicephalus ticks from the Iberian Peninsula and Africa. Our analyses detected several qPCR-positive signals for both SFGR and Babesia species, of which we suggest R. sanguineus-tropical lineage as a natural vector of Babesia vogeli and R. sanguineus- temperate lineage of SFGR. The acquisition of 190 CLE sequences allowed to evaluate co-phylogenetic associations between the tick and the symbiont. With this data, we observed a strong but incomplete co-cladogenesis between CLE strains and their Rhipicephalus tick lineages hosts. Abstract : Coxiella and Rhipicephalus mitochondrial lineages revealed an almost complete co-cladogenesis signature between ixodid lineages and endosymbiont strains, evidencing the strong co-evolutionary history between these taxa.